Clinical Impact of Secretion Retention - Ntoumenopoulos, George (Current Respiratory Medicine Reviews, 2014)
Secretion retention in the intubated and mechanically ventilated patient has been poorly described and investigated to date. There is no gold standard for the diagnosis or detection of secretion retention in the intubated and mechanically ventilated patient. Hence, the impact of secretion retention on patient outcomes is unknown and driven by either anecdote or opinion or by the use of surrogate measures. Surrogate measures such as the increased need for airway suctioning have been related to the increased re-intubation rates after elective extubation. In the intubated and mechanically ventilated patient secretion retention may impact on gas exchange, pulmonary complications such as atelectasis or pneumonia, endotracheal tube occlusion, need for change of artificial airway or therapeutic bronchoscopy or chest physiotherapy. Factors such as mucus volume, mucus viscosity, mucus depth, mucus location (peripheralised versus centralized secretions), patient factors (e.g. inspiratory and or expiratory muscle strength, pre-existing diseases such as COPD or neuromuscular disorders), and the interplay with intubation and mechanical ventilation or the combination thereof may determine whether patient outcomes are affected. In the intubated and mechanically ventilated patient the difficulties in the detection and monitoring the movement of secretions within the airways pose the greatest challenge to identifying the clinical impact and hence optimal methods to facilitate secretion clearance. This article will review the literature on secretion retention and patient outcomes in the intubated and mechanically ventilated patient.
Keywords: Mechanical ventilation